Prevalence of HIV sero-discordance and associated behavioural factors among couples aged 18-49 years from Matsapha in Swaziland - Ngwenya, Nkosingiphile Nkosinathi (My University, 2017)
Introduction: Sero-discordant couples are a population at risk for new HIV infection in Swaziland due to heterosexual transmission from an HIV-infected partner to the other. Male circumcision and condom use have been key HIV prevention strategies for negative partners. The overall objective of this study was to determine sero-discordance rate and behavioural factors associated with HIV status among couples aged 18-49 years from Matsapha in Swaziland in 2013. Methods: This is a secondary analysis of the Matsapha voluntary counselling and testing (VCT) couple dataset of 2013 in Swaziland. The aim of the routine VCT couple data collection was to assess HIV prevalence in Swaziland amongst couples, aged 18-49. In the routine VCT data collection, a blood sample for HIV testing was taken and a Swaziland HIV testing and counselling (HTC) client record form was administered to all individuals accessing the service as couples in 2013 in Swaziland. For this study the sample size was 214 couples. The sample was limited to men and women aged 18-49 years documented as couples (in a relationship) where HIV status was known for both partners. Logistic regression analyses were conducted to detect associations between demographic factors, female and male sero-discordant characteristics and risk factors (i.e. condom use, sexual transmitted infections (STIs), number of sexual partners in the past 6 months, male circumcision). Results: Of 214 couples identified in the Matsapha VCT dataset, couple HIV prevalence in this study was found to be 13.6%. Couple HIV prevalence was as follows: 86.4% were concordant negative, 7.5% were HIV sero-discordant and 6.1% were concordant positive couples. Of the 16 sero-discordant couples, 11 of the HIV positive partners were women. The most significant independent predictor of at least one partner being HIV-infected (versus both partners HIV-uninfected) was the male partner having two or more sexual partners (AOR= 7.6; 95% CI 1.7 to 34.5; P=0.01). In addition there was some evidence that couples who reported only using condoms “sometimes” were at a greater risk of HIV-infection than couples who reported condom use “always” (AOR= 3.2; 95% CI 0.8 to 12.5 ; P=0.09). Conclusions: Overall, the findings in this study show positive associations between two or more sexual partners and the outcome variable of HIV infection. The study indicated that couple HTC programs should help HIV negative partners in sero-discordant relationships remain uninfected by promoting faithfulness to one sexual partner.
A research report submitted to the School of Public Health, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the Degree of Master of Public Health.
Keywords: HIV